Acts of the General Assembly and Ordinances of the Trustees for the Organization and Government of the University of North Carolina 15 (1838) - (:unkn) unknown (My University, 1838)
Ch. 5, § 13: Prohibited students from keeping any firearms or gunpowder at the college. Prohibited keeping, carrying, or owning any sword, dirk, sword-cane, or other deadly weapon. Prohibited use of firearms without the permission of the college president.
Keywords: SENSITIVE PLACES; POSSESSION; GUNPOWDER - STORAGE